Prototype Sistem Monitoring Siswa Menggunakan Teknologi RFID (Radio Frequency Identification) dan Sms Gateway Berbasis Client Server (Studi Kasus : SMA Santo Paulus Pontianak) - Susanti, Susi (Jurusan Informatika Universitas Tanjungpura, 2014)
Student monitoring is an activity undertaken by school and parents in monitoring their children at school. Each school have many different ways to monitor. Some of them do it manually and the others use computer and technology that helps them. Monitoring that carried out by Santo Paulus Pontianak such as the presence of student, extracurricular, and homework. They did it manually. The school provides information to parents by mail or telephone. Monitoring will goes well when there is technology that supports it. The technology that can be used to help monitor are RFID (Radio Frequency Identification) and sms gateway. RFID is a technology taht uses radio waves to identify people or objects automatically. So that RFID is used as the student id card that can be identifu students while they are at school. And short message service (sms) gateway is a software that combines computer technology and mobile device technology, they are integrated with a database that has a specific purpose. Sms gateway also helps parents to know their children activities through the notification that send to their phone. The testing result show that the monitoring system can help their parents and school to monitor students.